Evaluation of the competitiveness of agro-industrial cooperatives: a case study in Goiás state, Brazil - Oliveira Junior, Osmar de Paula; Wander, Alcido Elenor (Revista de Administração da UFSM, 2025)
Purpose/objective: This study examines the application of the Cooperative Competitiveness Index (CCI) Model as a tool for measuring the competitiveness of agro-industrial cooperatives. Design/methodology/approach: This study investigated two cooperatives by analyzing key sub-factors and drivers of competitiveness, using one as a benchmark and the other as the subject of assessment. Quantitative sub-factors were compared between the cooperatives, while qualitative ones were evaluated through a structured questionnaire with closed yes/no questions. Findings: The results indicate that the assessed cooperative demonstrates local-level competitiveness; however, it faces several challenges that require strategic improvements. The findings support the CCI Model as a viable and promising tool for enhancing competitiveness management in agro-industrial cooperatives. Research limitations/implications: This study considered only two cooperatives. Therefore, it is essential to further test this recent, promising tool (CCI Model) to ensure it provides practical management insights on aspects that cooperative management should focus on to improve the cooperative’s competitiveness. Originality/value: This is the first known application of the CCI Model in practice, yielding valuable insights for the management of agricultural cooperatives to enhance their competitiveness in their respective sectors.